Development of a Web-Based Management Information System for Student Creativity Program (PKM) Using Extreme Programming and Laravel Framework - Rahmah, Nihayatur; Hidayat, Nurul; Wibowo, Dwi Kurnia (Informatika, Universitas Jenderal Soedirman, 2025)
This research originates from the absence of an integrated system for managing the Student Creativity Program (PKM) at the Faculty of Engineering, Universitas Jenderal Soedirman, which has caused inefficiencies in archiving, monitoring, and reporting. To address this problem, a web-based management information system was developed using the Extreme Programming (XP) methodology, selected for its flexibility, iterative process, and strong user involvement. The novelty of this study lies in the development of a system specifically designed for PKM management at the faculty level, which has not been previously available. Unlike prior studies, the system not only supports proposal submission but also integrates review, scoring, revision, and progress monitoring. The development process followed the four main stages of XP: planning, design, coding, and testing, with active user participation in each cycle. Blackbox testing confirmed that all core features functioned properly. The implementation of this system has proven to enhance efficiency, transparency, and accountability, reduce administrative workload, and contribute to informatics by demonstrating the practical application of the XP methodology in developing academic information systems.